Diastolic function in Olympic athletes versus controls: Stiffness-based and relaxation-based echocardiographic comparisons - Apor, A.; Merkely, B.; Morrell, T.; Zhu, S.; Ghosh, E.; Vago, H.; Andrassy, P.; Kovacs, S. J. (Journal of Exercise Science & Fitness, 2013)
Physiologic hypertrophy of the athlete heart, compared to the heart of nonathletic controls, is characterized by an increase in the left ventricular (LV) chamber dimension, mass, and wall thickness. Comparisons of the diastolic function (DF) between athletes and controls have employed conventional echocardiographic transmitral flow (Doppler E-wave)-derived indexes such as the peak flow velocity and deceleration time (which are load-dependent) and obscure the mechanistic determinants (e.g., stiffness, relaxation, load) of E-wave. With a focus on stiffness and relaxation chamber properties, conventional kinematic model-derived and load-independent indexes of the DF were compared between athletes and controls in this study. Echocardiographic and magnetic resonance imaging (MRI) data from 22 master athletes (whose sport was canoeing) and 21 sedentary controls were analyzed (1290 Doppler E-waves; 702 from athletes and 588 from the controls; on average, there were 30 pieces of data per subject). The LV mass and chamber size were determined from the MRI data. Quantitative DF assessment utilized an established kinematic model of filling that used the digitized Doppler E-wave contour as the input and characterized the DF on the basis of the chamber stiffness (k), relaxation/viscoelasticity (c), load (xo). We observed significant chamber stiffness (k), load (xo), and E-wave duration differences between the two groups. Concordant with the findings of previous studies, we also noted significant group differences in LV mass and dimension. These results indicated that physiological LV remodeling of the athlete heart at rest generates numerically quantifiable alterations in specific chamber properties. Assessment of the DF by using these methods during exercise will further elucidate the dynamic interplay between relaxation and stiffness as DF determinants.